Work-life balance of employees working in power sectors of krishnagiri district - Sathiya Priya, A; D. Muruganandam, Dr (International Journal of Engineering and Technology, 2018)
The purpose of this study is to highlight the necessity of adopting work-life balance in a power sector. The paper examines different elements of work-life balance especially with reference to employees working in power sectors. The main objective of the study is to study the work- life balance and work satisfaction of the employees in power sector. Based on the empirical evidence, the study proposes that there is a need for focusing on factors that aid in enhancing the work-life balance among employees. The data for the study was collected from 100 employees working in a power sector of Krishnagiri District of TamilNadu. The data collected were analyzed and interpretation and it’s derived by using tests like t-test, simple percentage analysis. The findings imply that employees expect rewards, awarding policies, special training, and stress less work from the company. Hence the study helped to find out the work- life balance among employees working in power sector.
Keywords: Work Place; Work-Life Balance; Work Environment; Fringe Benefits; Employee Training.